Evaluation of anti-diabetic properties of cosmos Caudatus leaves in obese-diabetic induced rats - Khatib, Alfi; Perumal, Vikneswari; Abdul Hamid, Azizah; Saari, Khozirah; Nik Jusoh, Nik Idris (2015)
Diabetes mellitus type-2 prevalence is increasing rapidly worldwide. It is resulted from the combination of impaired insulin secretion with reduced insulin sensitivity of the target tissues. The objective of this study is to evaluate the differences of metobolites profile in the serum of rats in different conditions (healthy, diabetes, Cosmos caudatus and metformin treated) using NMR based-metabolomics approach. The ethanol 80 % extract of C. caudatus was force fed to diabetic rats. Streptozotocin was used to induce the obese rat to become diabetic (ob-db). Rats were divided into four groups: healthy rat, ob-db treated with 300 mg/kg metformin and ob-db treated with 200 mg/kg of C. caudatus. The NMR serum spectra of rats were statistically correlated using multivariate data analysis to discriminate the groups and to identify the metabolites responsible for discrimination. Glucose level which was elevated in type 2 diabetic rats can be reduced to the normal range. Interestingly metformin caused elevation of ethanol, lactate and alanine which were not observed in C. caudatus treated rats. Other significant metabolites which have been identified were glucose, ethanol, alanine and lactate. This study suggested that C. caudatus is potential for the treatment of type 2 diabetes.